REVIEW OF ENERGY MINIMIZATION TECHNIQUES IN WIRELESS SENSORS NETWORK - Mubel , Basantilal; Goyal , Dr. Sachin; Agrawal, Dr. Ratish (International Journal of Engineering Technologies and Management Research, 2018)
The current decade of technology trends adopted the utilization of wireless sensors network. The wireless sensors network integrates with cloud based services and facilitate in every field of social engineering. The success story of sensors based network is utilization of energy. The sensor devices occupied tiny battery for energy. If the energy utilization is not maintained the life of network is expire. In this paper present the review of energy based protocol used in wireless sensor network. The maximum utilization of energy during the sensing of data of sensors node. Some authors used dual duty cycle for the sensing of sensor data and transmit data to sink node.